(untitled) (The Nepali Mathematical Sciences Report, 2025)
Efficient operating room scheduling (ORS) is a cornerstone of modern healthcare delivery, directly impacting patient outcomes, resource utilization and hospital finances. In Kathmandu’s government hospitals, patients face surgical delays ranging from six months to two years due to manual scheduling processes that are time-consuming and inflexible. Drawing inspiration from a case study at Aichi Medical University in Japan, this work reviews their ORS model, which uses regression analysis and mixed-integer programming (MIP). Preliminary simulations demonstrate the system’s ability to schedule 5 operations across 3 rooms with 5 surgeons within a 180-minute window, achieving significant efficiency gains in just one second. This review explores the methodology, results, and transformative potential of this approach, with implications for global healthcare improvement.